Postoperative Pulmonary Hypertension After Complete Tetralogy of Fallot Repair: Mechanistic Determinants and Prognostic Implications for Early Clinical Outcomes - Damayanti , Eka; Tavianto, Doddy (Journal of Society Medicine, 2026)
Introduction: Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart disease, with an incidence of approximately three per 10,000 live births. Postoperative pulmonary hypertension following complete repair is a rare but life-threatening complication that may lead to weaning failure from cardiopulmonary bypass. This condition is driven by acute increases in pulmonary vascular resistance and impaired right ventricular–pulmonary arterial coupling. Recognized risk factors include chronic preoperative hypoxia, younger age at surgery, and severe right ventricular dysfunction. Case Description: A three-year-old child with stunted growth and longstanding cyanosis since infancy underwent evaluation, revealing a large malaligned ventricular septal defect, 50% overriding aorta, and severe pulmonary stenosis with a pressure gradient of 85 mmHg. Intraoperative findings confirmed a double-outlet right ventricle with multiple atrial septal defects. Following total correction, the patient was not weaned from cardiopulmonary bypass because of acute right ventricular failure and severe pulmonary hypertension. Atrial septal defect creation for decompression and maximal inotropic support with dobutamine, adrenaline, and milrinone were performed. Despite aggressive management, the patient progressed to refractory cardiogenic shock with an arterial pressure of 25/19 mmHg and died within 24 hours postoperatively. Conclusion: This case underscores the catastrophic impact of postoperative pulmonary hypertensive crises in patients with complex congenital heart disease. The failure of weaning from cardiopulmonary bypass due to acute right ventricular failure represents a critical inflection point associated with extremely high mortality. Early risk stratification, perioperative optimization, and timely consideration of advanced mechanical circulatory support are essential. The integration of targeted pulmonary vasodilator therapy with vigilant hemodynamic monitoring may improve right ventricular adaptation and clinical outcomes in high-risk patients.